A Study on the Need for VBI in Malaysian Islamic Financial Industry and its Shari'ah Perspective - Khan, Mohammad Bilal (El-Barka Journal of Islamic Economics and Business, 2021)
The purpose of this paper is to highlight the need for Value-Based Intermediation (VBI) in Malaysia introduced by Bank Negara Malaysia (BNM) in March 2018, under the guidance of Shari'ah Advisory Council (SAC), which is the decisive authority in matters relating to Shari'ah, analyse the aim of VBI against that of SDGs in the light of Maqasid al-Sahri'ah, and to assess VBI from the perspective of Shari'ah. The growth of Islamic banking in Malaysia experienced a boost where the market share of Islamic banking assets grew from 7.1% in 2010 to 28% in 2016, but there has been a decline in Islamic finance's annual growth from 24.2% in 2011 to only 8.2% in 2016. There could be various reasons for this decline, such as maintaining a steady growth requires constant innovation in the products and services offered. However, innovation becomes difficult in case of IFIs, since they have to comply with legal and Shari'ah rules at the same time. Qualitative method of study is used for this paper.  It is found in the study that VBI not only conforms with the principles of Shari'ah but also re-focuses IFIs to achieve the objectives of Shari'ah or fulfill Maqasid al-Shari'ah. The study also found that VBI is also in line with the SDGs, which are human-made goals presented to the world by United Nations around 2012. However, while SDGs are prone to changes and criticism, the objectives, or goals of Shari'ah are holistic, permanent, and divine. VBI is a concept applicable only in Malaysia's Islamic Finance Industry until the time this paper is written, and therefore, it focuses only on the Malaysian IFI. There is a need to understand why VBI was needed in Malaysian IFI despite each Islamic bank having their own Shari'ah committee and SAC of BNM and this paper will help develop that understanding.